Developing Plugin e-DDC as an Additional Application for Senayan Library Management System with PHP Language Programming and MySQL Database - Rotmianto, Mohamad; Wahyudi, Eko (Record and Library Journal (Online), 2018)
Between Senayan Library Management System or usually called SLiMS and e-DDC (electronic Dewey Decimal Classification) now is the most popular library application software which has a lot of user, because it is simple to use, has an updating guarantee from its developers and off course both of them are free of charge. Although SLiMS and e-DDC are different application at all, as practically they are recommended to be used togather for library management. SLiMS is used for library automation and e-DDC is to find collection’s classification. Many users of SLiMS and e-DDC ever give suggestions about developing SLiMS with e-DDC include in its database, and then librarians will be easier to manage their libraries. Because of that suggestion, finally a plugin as an additional application for SLiMS has been created and developed. That plugin was build with PHP language programming and MySQL database. The purpose of this paper is to enrich about reference of development of library application, especially those based on Free Open Source Software (FOSS). This paper use Research and Development Methods. And the result of this paper is Plugin e-DDC for SLiMS which has released on May, 2nd 2015, in order to celebrate “National Education Day”.